1991
DOI: 10.1002/aja.1001920206
|View full text |Cite
|
Sign up to set email alerts
|

Testis structure in the sys (symplastic spermatids) mouse

Abstract: Testes of mice with the recessive insertional mutation termed symplastic spermatids (sys) were assessed for structural and developmental abnormalities. Homozygous (sys/sys) males are infertile due to an abnormality in spermatogenesis leading to azoospermia. The major interruption to spermatogenesis occurs when the intercellular bridges that connect round spermatids open prematurely resulting in the formation of symplasts. Symplasts contain as many as 285 nuclei. Development of spermatids within symplasts is ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The present results are in agreement to (Russel et al 1991) who described that it takes around 13 days to a single A spermatogonia from starting division until becoming an elongated spermatid. In this study, the germ cell transplant showed to be an effective method to recover spermatogenesis in degenerated rat testis caused by Busulfan treatment.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…The present results are in agreement to (Russel et al 1991) who described that it takes around 13 days to a single A spermatogonia from starting division until becoming an elongated spermatid. In this study, the germ cell transplant showed to be an effective method to recover spermatogenesis in degenerated rat testis caused by Busulfan treatment.…”
Section: Discussionsupporting
confidence: 96%
“…A single A spermatogonia (As) is the stem cell of spermatogenesis. After a number of spermatogonial divisions, this cell gives rise to spermatocytes, which after meiotic divisions, produce spermatids that develop into spermatozoa (Russel et al, 1991). The process of regeneration through stem cells in the testis was described in mice exposed to neutron radiation (Meistrich et al, 1978).…”
Section: S Permatogenesis Is a Very Complex Cellular Process In-mentioning
confidence: 99%
“…Symplasts originate when the intercellular bridges between round spermatids collapse and form a multinucleated cell that displays arrested development. These symplasts eventually undergo degeneration and are phagocytised by Sertoli cells and intratubular macrophages 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Multinucleated giant cells may be more prevalent among immature animals; only frequency levels occurring noticeably beyond those among concurrent control animals should be recorded. In the sys mouse, the major interruption to spermatogenesis occurs when the intercellular bridges that connect round spermatids open prematurely resulting in the formation of symplasts (MacGregor et al 1990;Russell et al 1991 If it is unilateral, the probable cause is efferent duct blockage. The efferent ducts are the major site of reabsorption of seminiferous tubule fluid, which is secreted by the Sertoli cells (Hess 2002).…”
Section: Degeneration Tubular (Figures 6-8): Testismentioning
confidence: 99%